Verification of medium-range MJO forecasts with TIGGE - Matsueda, M; Endo, H (2011)
The Madden-Julian oscillation (MJO) is the dominant mode of intraseasonal variability in the tropics. Accurate simulations of the MJO are important for studies of weather and climate in the tropics and extratropics. This study assesses the forecast performance of operational medium-range ensemble forecasts, available at THe Observing system Research and Predictability EXperiment (THORPEX) Interactive Grand Global Ensemble (TIGGE) data portal, regarding the MJO for the past 3 years. The results indicate that ECMWF (European Centre for Medium-range Weather Forecasts) and UKMO (United Kingdom Meteorological Office) generally yield the best performances in predicting the MJO; however, they do not always show similar skills. ECMWF performs well in simulating the maintenance and onset of the MJO in phases 1-4, whereas UKMO and NCEP (National Centers for Environmental Prediction) perform well in simulating the maintenance and onset of the MJO in phases 5-8. Thus, the best-performing numerical weather prediction (NWP) centre varies with the phase of the MJO. With advance knowledge of the forecast characteristics of each NWP centre, we can ensure more reliable forecasts of the MJO in operational uses, based on the MJO phase. This represents an advantage of the multi-centre grand ensemble approach. Copyright 2011 by the American Geophysical Union.